Integration of Spiritual and Cognitive Dimensions in Hadith Learning Jala'ul Afkar - Hasan, Moch. Sya'roni; Sintasari, Beny; Mujahidin, Mujahidin; Riza, Julianne Kamilia (LP3M STIT Al Urwatul Wutsqo Jombang, 2025)
This study analyzes the implementation of the Jala'ul Afkar Hadith memorization system in improving the spiritual intelligence and memory of students at the Al-Washoya Kertorejo Ngoro Jombang Islamic Boarding School. Using a qualitative approach with interviews, observation, and documentation methods, this study examines the hadith learning process that combines aspects of memorization, understanding, and internalization of values. The hadith memorization system is implemented through three stages: preparation, implementation, and deposit. The learning methods used are bandongan and talaqqi. The results of the study indicate that the implementation of the Jala'ul Afkar Hadith memorization system plays a significant role in improving the spiritual intelligence of students, especially in the aspects of piety and patience. The memorization process also contributes to improving cognitive abilities through organizing information, automation, and optimizing short-term knowledge storage capacity. Obstacles in implementing this system include difficulty in memorizing for students who are not serious, students' laziness in memorizing lessons, and loss of memorization because they are not repeated routinely. This study provides theoretical contributions to the discourse of integration of neuroscience and traditional Islamic education, as well as practical contributions in the form of a learning model that can be a prototype for other Islamic boarding schools in optimizing the potential of spiritual intelligence and memory of students.